The theory of large-scale ocean circulation - Samelson, R. M. (Cambridge University Press, 2011)
Mounting evidence that human activities are substantially modifying the Earth's climate brings a new imperative to the study of the ocean's large-scale circulation. This textbook provides a concise but comprehensive introduction to the theory of large-scale ocean circulation, as it is currently understood and established. Students and instructors will benefit from the carefully chosen chapter-by-chapter exercises. This advanced textbook is invaluable for graduate students and researchers in the fields of oceanic, atmospheric and climate sciences and other geophysical scientists, as well as physicists and mathematicians with a quantitative interest in the planetary fluid environment